Photogenerator of trichloroacetic acid--a perspective detritylation agent for microchip oligonucleotide synthesis - Siniakov, A N; Nikolaenkova, E B; Os'kina, I A; Savel'ev, V A; Samsonov, V A; Tikhonov, A Ia; Palatkina, M Iu; Zaĭtsev, D E (Bioorganicheskaia khimiia, 2014)
For the purpose of new detritylation agents search for microarray oligonucleotide synthesis we investigated applicability of [4-(4-methoxyphenyl)-2,6-dinitro-phenyl](phenyl)methyl 2,2,2-trichloroacetate for 4,4'-dimethoxytrityl group detritylation during oligonucleotide syntheses generating trichloroacetic acid at radiation by light with a length of wave of 405 nanometers. [4-(4-Methoxyphenyl)-2,6-dinitro-phenyl](phenyl)methyl 2,2,2-trichloroacetate has been successfully used for solid-phase oligonucleotide synthesis of desired oligonucleotides.